1995
DOI: 10.1002/ijc.2910610424
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of ex vivo‐activated memory T‐cell subsets with cyclophosphamide provides effective tumor‐specific chemoimmunotherapy of advanced metastatic murine melanoma and carcinoma

Abstract: Autolymphocyte therapy (ALT) is adoptive cellular therapy of neoplastic disease using ex vivo activation of autologous (human) or syngeneic (murine) lymphocytes from tumor-bearing hosts (TBH) by low doses of anti-CD3 monoclonal antibody (MAb) and a mixture of previously prepared autologous cytokines (T3CS). Ex vivo activation by T3CS without tumor antigen results in expansion of CD44+ (memory) T cells. These memory T cells (ALT cells) mediate in vivo anti-tumor specificity and with cyclophosphamide (CY) are ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…These observations may imply activation of anti-tumor immunity since CD45RO+ represents T memory subset while CD68+ is the marker of monocyte/macrophage [23] . Anti-CD3Ab can activate CD45RO+ T subset [24] , so we deduced that the increase of CD45RO+ cells in the tumor locals may come from CIK.…”
Section: Discussionmentioning
confidence: 91%
“…These observations may imply activation of anti-tumor immunity since CD45RO+ represents T memory subset while CD68+ is the marker of monocyte/macrophage [23] . Anti-CD3Ab can activate CD45RO+ T subset [24] , so we deduced that the increase of CD45RO+ cells in the tumor locals may come from CIK.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that cyclophosphamide potentiates the antitumor activities of a number of immunotherapeutic strategies (25,39). The immunomodulatory effects of cyclophosphamide are not fully understood, but several mechanisms have been proposed, including enhanced expansion of antigenspecific T cells (40); stimulation of innate immune response, in particular the activation of dendritic cells (41); induction of type I IFN (42); Th2/Th1 shift in cytokines profile (27); and elimination/inhibition of regulatory T cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophosphamide is a widely known chemotherapeutic agent (21) that has been used by several groups, including ours, as an immunomodulatory agent against murine and human cancers (22)(23)(24)(25). We have previously shown that a single lowdose cyclophosphamide can inhibit the metastasis of a B-cell lymphoma (L-TACB) in a rat model, likely due to the induction of potent immunomodulatory mechanisms that result in a significant reduction in IL-10 levels (26).…”
mentioning
confidence: 99%
“…Key Words: CD8 + T cells, CD11b, cyclophosphamide, dsRNA, dendritic cells, IFN, Ly6G, myeloid cells, OVA, OT-1 T cells, poly (I:C), TLR3, vaccine (J Immunother 2007;30: [40][41][42][43][44][45][46][47][48][49][50][51][52][53] A critical component of antitumor immunity is the development of effector T cells that can survive longterm as functional memory T cells. It is currently believed that naive T cells are programmed to expand dramatically after antigen encounter.…”
mentioning
confidence: 99%